Spatial distribution characteristics of soil salinity and nutrients in saline soil based on farm scale - Ma, Yue; Zhang, Kaiyue; Zhang, Xiaoguang; Liu, Xinwei (Frontiers in Sustainable Food Systems, 2025)
IntroductionSoil salinity in the Yellow River Delta exhibits seasonal dynamics, with desalination in October (low-salt period) and salinity return in April (high-salt period).MethodsThis study quantified the spatiotemporal variations in soil salinity, alkaline nitrogen (AN), available phosphorus (AP), and available potassium (AK) in mild saline soils (0-20 cm depth) at a 72.3 hm2 farm scale using grid sampling, classical statistics, and geostatistics (semi-variance analysis, ordinary kriging)ResultsThe key results showed that the mean soil salinity was higher in April than in October; all indices displayed moderate variability, where the coefficient of variation (CV) of salinity was higher in October than in April, while the CV values of AN, AP, and AK were lower in October than in April; salinity (in both periods), AK (in both periods), and AP (in October) exhibited weak spatial dependence (C0/(C0+C) > 75%) under the influence of random factors, and AN (in both periods) and AP (in April) showed moderate spatial dependence (25% < C0/(C0+C) < 75%) driven by both structural and random factors. Spatial distribution maps revealed patchy patterns, with salinity, AN, and AP contents being higher at field edges. In October, except for the southern part with high AK content, the AK content at the edges was lower than that in the central area; in April, AK was distributed in rings, and its content generally increased from the middle to the four sides.DiscussionThese high-resolution farm-scale study results provide data support for precise nutrient management of saline soils during low-salinity and high-salinity periods.